PENDIDIK HEBAT, PENDIDIKAN BERKUALITAS : ANALISIS KOMPETENSI GURU DI ERA MODERN - Tiara Dwi Saputri; Abdul Khobir; Mila Ainurrahma; Safira; Muhammad Sabiq Almuaffaq (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
The demands on educators today are becoming more complex with the development of digital technology and the rapid pace of globalization. This study attempts to examine the competencies of teachers, changes in teaching methods, emerging difficulties, and the crucial importance of establishing standards and a cooperative educational environment to achieve quality education. The approach used in this study is a literature study, which includes the collection, review, and evaluation of 30 scientific journal articles related to the topic of teacher competency and professionalism in the digital era. The results of the study indicate five crucial aspects: (1) high-achieving educators are required to integrate four core capabilities with strong dedication; (2) there is a shift in the teaching mindset towards the figure of a future educator who masters technology; (3) the implementation of technology faces obstacles in the form of teacher abilities, limited facilities, time, and interaction; (4) the establishment of standards and transformational leadership are determining factors for improving the quality of global education; and (5) the success of contemporary education requires harmony between educators, parents, and the community (the concept of the tri-center of education). This study concludes that improving the quality of education at the national level cannot solely depend on the personal abilities of teachers, but also requires integrated systematic support.